Nexus between foreign direct investment, foreign aid, foreign remittance and economic growth in Bangladesh: Analysis of association - Zobair, Shah Asadullah Mohd.; Uddin, Myne (IIUC Studies, 2020)
This study aims at exploring time series data of economic growth indicator and foreign inflow of fund to Bangladesh to investigate the nature of impact of such fund inflows on economic growth. In this regard data has been collected from World Bank data base for a period ranging from 1976 to 2017. The analysis is conducted by using the ARDL approach. The study identified foreign direct investment as a crucial external factor for growth of Bangladeshi economy. But another two mentionable ways of fund inflow such as foreign aid and remittance are found to play negative role in this regard. Along with these findings, this study recommends that the competent authority of Bangladesh should focus on creating more investment friendly environment to attract and ensure continual of foreign investment. Additionally, the study also claims for proper action to ensure effective use of policy and rules to make the best use of foreign aid and ensure enhanced capital formation of the foreign remittance. IIUC Studies Vol.16, December 2019: 77-98